The role of YAP1 in survival prediction, immune modulation, and drug response: A pan-cancer perspective - Hu, Xueqing; Zhang, Yingru; Yu, Hao; Zhao, Yiyang; Sun, Xiaoting; Li, Qi; Wang, Yan (Frontiers in Immunology, 2022)
Dysregulation of the Hippo pathway has been implicated in multiple pathologies, including cancer. YAP1 is the main effector of the pathway and has been reported to be pervasively activated in human malignancies. In the current study, we evaluated YAP1’s role in prognostic value, immune modulation and drug response in a pan-cancer perspective. We downloaded the transcriptional RNA-sequenced data, genome-wide DNA methylation levels (DNA Methylation 450K) and clinical characteristics from public UCSC Xena database. Then we compared the YAP1 expression between normal and cancerous tissues and among different pathologic stages. Survival analyses were conducted to assess the prognosis value of YAP1 in predicting the clinical outcome of patients. Gene Set Enrichment Analysis software was used to compare the 50 hallmark gene sets difference between patients with high YAP1 and those with low YAP1 expression. Additionally, we performed the correlation analyses between YAP1 expression and RNA modification-related gene expression, tumor mutation burden (TMB), microsatellite instability (MSI), immune checkpoint gene expression and infiltration of immune cells. IC50s (half-maximal inhibitory concentration) and gene expression of cancer cell lines were downloaded from the CellMiner database to calculate the correlation between YAP1 expression level and IC50 of 218 FDA-approved drugs and 574 drugs in clinical trial. We found that YAP1 is aberrantly expressed in various cancer types and is regulated by its DNA methylation and posttranscriptional modification, especially m6A methylation. High-expressed YAP1 is associated with poor survival outcome of ACC, BLCA, LGG, LUAD, PAAD. YAP1 mRNA expression is negatively correlated with the infiltration of CD8+ T lymphocytes, T follicular helper cells and activated NK cells in pan-cancer. Higher YAP1 expression showed upregulation of TGF beta signaling, Hedgehog-signaling and KRAS signaling. IC50s of FDA-approved chemotherapeutic drugs that are able to inhibits DNA synthesis, including Teniposide, Dacarbazine, Doxorubicin etc. and inhibitors of Hypoxia-inducible factor, MCL-1, ribonucleotide reductase and FASN in clinical trials are negatively correlated with YAP expression level. In conclusion, YAP1 is a potential biomarker for the prognosis and play immunosuppressive and cell proliferation-stimulating roles in pan-cancer. Some chemotherapeutic drugs that were FDA-approved or in clinical trial might be effective on cancer patients with high YAP1 expression.